If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n + n = -2 Combine like terms: n + n = 2n 2n = -2 Solving 2n = -2 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Divide each side by '2'. n = -1 Simplifying n = -1
| 2n+2=-50 | | 6(2x-9)=28 | | N*3=36 | | 48=n | | x+x+8=332 | | N+32=45 | | .02(x+3)-4(2x-3)=3.4 | | 3k+6=k | | (9x^2-18x+5)= | | -4x+-3y=30 | | -5=-19 | | 2y+4=38 | | g=2+6t | | n^6=6 | | 5-2y=1.5 | | 9x-6=3x-30 | | 7a+4=5a+8 | | 7(b-5)+12=5 | | 16Y=15(y+13) | | 4f-2=18 | | -107=3+10x | | 0.04(12)+0.01x=0.02(12+x) | | 2x-18=5x+12 | | -7(3x+9)=-21x+63 | | n+21=24 | | 4x+b=3x+7 | | 5(5x-20)=25(x-20) | | 8y-8=37-7t | | 9x^2-18x+5= | | y-6=x | | 8850=x^2-14x+63 | | 4y-9+y+20=5y+20-3y |